Modified polyethylene double-wall corrugated pipe material and preparation method thereof

By using high-density polyethylene, rare earth compounds and other modifiers in the double-wall corrugated pipe material, and through grafting reaction and hydrolytic crosslinking reaction, modified polyethylene double-wall corrugated pipe material with high thermal stability, mechanical properties and flame retardant properties are prepared, solving the problem of insufficient thermal stability and fire resistance of existing materials in high-temperature environments.

CN119505402AInactive Publication Date: 2025-02-25YUNNAN FANGTE ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411668551.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing double-wall corrugated pipe materials lack thermal stability and fire resistance in high-temperature environments and fire-prone environments, and lack high-strength modified materials specifically used in the industrial field.

Method used

The modified polyethylene double-wall corrugated pipe material is prepared by grafting reaction and hydrolyzed crosslinking reaction.

Benefits of technology

It significantly improves the thermal stability, mechanical properties and flame retardant properties of the material, making it difficult to decompose under high temperature environments, and has good impact resistance and flame retardant properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a modified polyethylene double-wall corrugated pipe material and a preparation method thereof, and the pipe material comprises the following raw materials by weight: 70-80 parts of high density polyethylene, 10-15 parts of linear low density polyethylene, 0.5-2 parts of a crosslinking modifier, 0.5-1 part of dicumyl peroxide, 0.1-0.5 part of a main antioxidant, 0.1-0.3 part of an auxiliary antioxidant, and 5-10 parts of a flexibilizer. The invention relates to a high-strength high-toughness alloy which comprises the following components in parts by weight: 2-3 parts of lanthanum fluoride (LaF3), 2-3 parts of cerium fluoride (CeF3), 3-5 parts of SMC crystal whiskers, 3-5 parts of basic magnesium sulfate crystal whiskers coated with tannic acid and 6-10 parts of zinc borate crystal whiskers. The rare earth compound lanthanum fluoride, the lanthanum fluoride, the SMC whisker, the basic magnesium sulfate whisker coated by tannic acid and the zinc borate whisker are added, so that the thermal stability and the mechanical property of the material can be greatly improved, and the material is not easy to decompose at a relatively high temperature; and the cerium compound and the zinc borate whisker can catalytically esterify into carbon when the polyethylene is combusted, and a compact and continuous carbon layer is quickly formed on the surface of the polyethylene, so that the flame retardant property of the polyethylene is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer material pipelines, in particular to a modified polyethylene double-wall corrugated pipe material and a preparation method thereof. Background Art

[0002] The double-walled corrugated pipe is composed of two layers of inner and outer walls. The outer wall is annularly corrugated, which increases the ring stiffness of the pipe and enables it to withstand greater external pressure. The inner wall is smooth and flat, which reduces the resistance of the fluid in the pipeline and improves the transportation efficiency. It can be seen that its main design direction is to have greater strength and mechanical properties. In industrial fields such as chemical, pharmaceutical, and food, double-walled corrugated pipes can be used to transport various corrosive media and wastewater, and many scenes in these industrial fields are high-temperature environments or fire-prone environments. However, the polyethylene modified ingredients and processes used in the double-walled corrugated pipe materials on the market are relatively simple, and the thermal stability and fire resistance are not outstanding. There is a lack of a high-strength modified material for double-walled corrugated pipes specifically for the industrial field, taking into account excellent thermal stability and fire resistance. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a modified polyethylene double-wall corrugated pipe material to solve the technical problems in the above-mentioned background technology.

[0004] The technical solution of the present invention is:

[0005] A modified polyethylene double-wall corrugated pipe material comprises the following raw materials in weight ratio: 70-80 parts of high-density polyethylene, 10-15 parts of linear low-density polyethylene, 0.5-2 parts of a cross-linking modifier, 0.5-1 parts of dicumyl peroxide, 0.1-0.5 parts of a primary antioxidant, 0.1-0.3 parts of an auxiliary antioxidant, 5-10 parts of a toughening agent, 2-3 parts of lanthanum fluoride (LaF3), 2-3 parts of cerium fluoride (CeF3), 3-5 parts of SMC whiskers, 3-5 parts of basic magnesium sulfate whiskers coated with tannic acid, and 6-10 parts of zinc borate whiskers.

[0006] Furthermore, the cross-linking modifier is vinyltrimethoxysilane (VTMO) or vinyltriethoxysilane (VTEO).

[0007] Furthermore, the main antioxidant is a hindered phenol antioxidant and the auxiliary antioxidant is a phosphite.

[0008] Furthermore, it also includes 0.2-0.5 parts of hindered amine light stabilizer.

[0009] Furthermore, it also includes 5-10 parts of light calcium carbonate with a particle size of 1-5 μm and 1-2 parts of titanate coupling agent.

[0010] Furthermore, the toughening agent is ethylene-vinyl acetate copolymer.

[0011] Furthermore, it also includes a lubricant, which is calcium stearate, and the added amount is 0.5-1.5 parts.

[0012] The present invention also provides a method for preparing the modified polyethylene double-wall corrugated pipe material, comprising the following steps:

[0013] (1) Weigh the raw materials of each component according to the amount;

[0014] (2) placing high-density polyethylene particles and linear low-density polyethylene particles in a freeze dryer and cooling them to below -50°C;

[0015] (3) The polyethylene particles become brittle and hard after cooling, and are taken out and put into a ball mill for crushing. The crushed polyethylene powder is taken out from the equipment and passed through a 200-mesh sieve to obtain polyethylene powder of the desired particle size range;

[0016] (4) The polyethylene powder obtained in step 3 is mixed with a cross-linking modifier, a primary antioxidant, an auxiliary antioxidant, and dicumyl peroxide in proportion, and then a grafting reaction is carried out in a reactor to obtain a grafted polyethylene powder. The reaction temperature is 150-200° C. and the reaction time is 10-20 min. During the reaction, continuous stirring is required to ensure that the materials are evenly mixed;

[0017] (5) adding the remaining raw materials in sequence, and then continuing to stir and mix, and maintaining the temperature at 150-200° C., so that the remaining components are evenly coated on the periphery of the grafted polyethylene powder;

[0018] (6) extruding the grafted polyethylene powder through an extruder;

[0019] (7) The extruded product is immersed in warm water at 70-90°C to carry out a hydrolysis and cross-linking reaction.

[0020] The present invention is beneficial in that:

[0021] The present invention adds rare earth compounds lanthanum fluoride and lanthanum fluoride, which not only have very stable chemical and thermal properties, but also can improve thermal stability and mechanical properties after adding lanthanide compounds, making it less likely to decompose at higher temperatures. The cerium compound can catalyze esterification into carbon when polyethylene burns, quickly forming a dense and continuous carbon layer on the surface of polyethylene, thereby improving the flame retardant properties of polyethylene.

[0022] The addition of SMC whiskers and tannic acid coated basic magnesium sulfate whiskers can comprehensively improve the rigidity and strength. Zinc borate whiskers can catalyze esterification into carbon during the combustion process. The carbon layer can isolate the transfer of oxygen and heat, thereby playing a flame retardant role and improving the flame retardant properties of polyethylene. DETAILED DESCRIPTION

[0023] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0024] Embodiment 1:

[0025] A modified polyethylene double-wall corrugated pipe material comprises the following raw materials in weight ratio: 70 parts of high-density polyethylene, 10 parts of linear low-density polyethylene, 0.5 parts of vinyl trimethoxy silane (VTMO), 0.5 parts of dicumyl peroxide, 0.1 parts of hindered phenol antioxidants, 0.1 parts of phosphites, 5 parts of ethylene-vinyl acetate copolymer, 2 parts of lanthanum fluoride (LaF3), 2 parts of cerium fluoride (CeF3), 3 parts of SMC whiskers, 3 parts of basic magnesium sulfate whiskers coated with tannic acid, and 6 parts of zinc borate whiskers.

[0026] The present invention adds rare earth fluorides lanthanum fluoride (LaF3) and cerium fluoride (CeF3). The chemical and thermal properties of lanthanum fluoride (LaF3) are very stable. After adding lanthanide compounds, the thermal oxygen decomposition temperature of polyethylene in a high temperature environment will be increased, making it less likely to decompose at higher temperatures. In addition, the mechanical properties of polyethylene can be enhanced to a certain extent, such as improving the tensile strength and bending strength of the material, making the polyethylene products more durable.

[0027] Cerium has good flame retardant properties, and adding cerium-containing compounds to polyethylene can play a flame retardant role. It can catalyze esterification into carbon when the polymer material burns, and quickly form a dense and continuous carbon layer on the surface of polyethylene, isolating the combustible gas inside the polymer material from contact with oxygen, preventing further combustion, and thus improving the flame retardant properties of polyethylene.

[0028] At the same time, cerium also has a positive effect on the aging resistance of polyethylene. It can enhance the weather resistance of polyethylene, making it less likely for polyethylene to age and degrade due to factors such as light, heat, and oxygen during long-term use, thereby extending the service life of the material.

[0029] Rare earth compounds can be added to polyethylene as nucleating agents to promote the crystallization of polyethylene and increase the crystallinity and crystallization rate. The increase in crystallinity helps to improve the physical properties of polyethylene, such as hardness, strength, dimensional stability, etc.

[0030] At the same time, a certain proportion of SMC whiskers, tannic acid-coated basic magnesium sulfate whiskers and zinc borate whiskers are also added.

[0031] The presence of SMC whiskers can limit the movement of polyethylene molecular chains and increase the rigidity of the material. The bending strength of polyethylene modified by whiskers will be greatly improved.

[0032] The magnesium sulfate whiskers coated with tannic acid can absorb and disperse energy in the polyethylene matrix. When the material is impacted, the whiskers can prevent the expansion of cracks and improve the impact resistance of the material.

[0033] Zinc borate whiskers can catalyze esterification into carbon during the combustion process, promoting the formation of a carbon layer on the polyethylene matrix. The carbon layer can isolate the transfer of oxygen and heat, thereby playing a flame retardant role and improving the flame retardant properties of polyethylene.

[0034] The preparation method comprises the following steps:

[0035] (1) Weigh the raw materials of each component according to the amount;

[0036] (2) High-density polyethylene particles and linear low-density polyethylene particles are placed in a freeze dryer and cooled to below -50°C. The cooled polyethylene particles become brittle and hard. They are taken out and placed in a ball mill for crushing. The crushed polyethylene powder is taken out of the equipment and sieved through a 200-mesh sieve to obtain polyethylene powder in the desired particle size range. This method can obtain finer powder with a narrow particle size distribution; it will not cause thermal degradation or mechanical force to damage the molecular chain, and is very suitable for processing heat-sensitive and easily degradable polyethylene materials.

[0037] (3) The obtained polyethylene powder is mixed with a cross-linking modifier, a primary antioxidant, an auxiliary antioxidant, and diisopropylbenzene peroxide in proportion, and then a grafting reaction is carried out in a reactor to obtain a grafted polyethylene powder. The reaction temperature is 150-200° C. and the reaction time is 10-20 min. During the reaction, continuous stirring is required to ensure that the materials are evenly mixed. The primary antioxidant can capture free radicals generated by the polymer during processing and use to prevent oxidative degradation of the polymer. The auxiliary antioxidant mainly decomposes hydrogen peroxide and synergizes with the primary antioxidant to enhance the antioxidant effect. Diisopropylbenzene peroxide is used as an initiator to initiate the grafting reaction between the cross-linking modifier and the polymer.

[0038] This step is mainly for grafting reaction. Commonly used silane crosslinking modifiers include vinyl trimethoxy silane (VTMO) or vinyl triethoxy silane (VTEO). Silane crosslinking is achieved by mixing a silane crosslinking modifier containing a hydrolyzable silane group with polyethylene under certain conditions to graft the silane crosslinking modifier onto the polymer molecular chain. The main reaction formula is as follows:

[0039] Silane grafting reaction:

[0040] The polymer (such as polyethylene) molecular chain (R) reacts with a silane crosslinking modifier (RSiX3, X is usually a hydrolyzable group, such as methoxy, ethoxy, etc.) to graft the silane crosslinking modifier onto the polymer molecular chain.

[0041] The reaction formula is: R+RSiX3→R—SiX3 (grafted polymer).

[0042] (5) Add the remaining raw materials in sequence, and then continue to stir and mix. The temperature is maintained at 150-200° C., so that the remaining components are evenly coated on the periphery of the grafted polyethylene powder. Ethylene-vinyl acetate copolymer (EVA) is a commonly used toughening agent. EVA with a vinyl acetate content of 18-28%, such as DuPont's Elvax 260, is selected. EVA can significantly improve the toughness and impact resistance of the pipeline.

[0043] (6) extruding the grafted polyethylene powder through an extruder;

[0044] (7) The extruded product is immersed in warm water at 70-90°C for hydrolysis and cross-linking reaction. In the presence of water, silane is hydrolyzed to generate silanol groups. These silanol groups condense with each other or with active groups such as hydroxyl groups on the polymer molecular chain to form a cross-linked network between the polyethylene molecular chains, thereby improving its heat resistance, chemical resistance and mechanical strength.

[0045] Silane hydrolysis reaction:

[0046] In the presence of water, the hydrolyzable group (X) on the silane crosslinking modifier is hydrolyzed to generate a silanol group (Si—OH). The reaction formula is: RSiX3+3H2O→RSi(OH)3+3HX.

[0047] Cross-linking reaction:

[0048] The silanol groups react with each other or with active groups such as hydroxyl groups on the polymer molecular chain to form a three-dimensional network cross-linked structure. The reaction formula is: Si—OH+Si—OH→Si—O—Si+H2O; Si—OH+R—OH→Si—O—R+H2O.

[0049] Embodiment 2:

[0050] A modified polyethylene double-wall corrugated pipe material comprises the following raw materials in weight ratio: 75 parts of high-density polyethylene, 13 parts of linear low-density polyethylene, 1 part of vinyl trimethoxy silane (VTMO), 0.8 parts of dicumyl peroxide, 0.3 parts of hindered phenol antioxidant, 0.2 parts of auxiliary antioxidant, 8 parts of ethylene-vinyl acetate copolymer, 2.4 parts of lanthanum fluoride (LaF3), 2.5 parts of cerium fluoride (CeF3), 4 parts of SMC whiskers, 4 parts of basic magnesium sulfate whiskers coated with tannic acid, and 8 parts of zinc borate whiskers.

[0051] The preparation method is consistent with that in the example.

[0052] Embodiment 3:

[0053] A modified polyethylene double-wall corrugated pipe material comprises the following raw materials in weight ratio: 80 parts of high-density polyethylene, 15 parts of linear low-density polyethylene, 2 parts of vinyl triethoxysilane (VTEO), 1 part of dicumyl peroxide, 0.5 parts of a primary antioxidant, 0.3 parts of phosphites, 10 parts of a toughening agent, 3 parts of lanthanum fluoride (LaF3), 3 parts of cerium fluoride (CeF3), 5 parts of SMC whiskers, 5 parts of basic magnesium sulfate whiskers coated with tannic acid, and 10 parts of zinc borate whiskers.

[0054] The preparation method is consistent with that in the example.

[0055] Embodiment: 4:

[0056] On the basis of Examples 1-3, 0.2-0.5 parts of hindered amine light stabilizer are added. For pipes that may be exposed to sunlight, hindered amine light stabilizer (HALS), such as BASF's Tinuvin 770, can be added. It can effectively prevent polyethylene aging caused by ultraviolet rays and extend the service life of the pipe. The preparation method is consistent with the example.

[0057] Embodiment 5:

[0058] On the basis of Example 1-4, 5-10 parts of light calcium carbonate with a particle size of 1-5 μm and 1-2 parts of titanate coupling agent are added. Calcium carbonate (CaCO3) is a common filler. Calcium carbonate can reduce costs and improve the hardness and dimensional stability of the pipeline. In order to make calcium carbonate well dispersed in the polyethylene matrix, it may be necessary to add an appropriate amount of coupling agent, such as titanate coupling agent, to improve the interface bonding force between the filler and the polymer. The preparation method is consistent with the example.

[0059] Embodiment 6:

[0060] On the basis of Examples 1-5, a lubricant is added, wherein the lubricant is calcium stearate, and the addition amount is 0.5-1.5 parts. Calcium stearate is a lubricant, which can improve the fluidity of the material during processing, reduce the friction between the melt and the processing equipment, and make the extrusion process of the pipe smoother. The preparation method is consistent with the example.

[0061] The embodiments of the present invention are described in detail, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the scope of protection of the present invention.

Claims

1. A modified polyethylene double-wall corrugated pipe material, characterized in that: The invention comprises the following raw materials in weight ratio: 70-80 parts of high-density polyethylene, 10-15 parts of linear low-density polyethylene, 0.5-2 parts of a cross-linking modifier, 0.5-1 parts of dicumyl peroxide, 0.1-0.5 parts of a primary antioxidant, 0.1-0.3 parts of an auxiliary antioxidant, 5-10 parts of a toughening agent, 2-3 parts of lanthanum fluoride (LaF3), 2-3 parts of cerium fluoride (CeF3), 3-5 parts of SMC whiskers, 3-5 parts of basic magnesium sulfate whiskers coated with tannic acid, and 6-10 parts of zinc borate whiskers.

2. The modified polyethylene double-wall corrugated pipe material according to claim 1, characterized in that: The cross-linking modifier is vinyl trimethoxy silane (VTMO) or vinyl triethoxy silane (VTEO).

3. The modified polyethylene double-wall corrugated pipe material according to claim 1, characterized in that: The main antioxidant is a hindered phenol antioxidant, and the auxiliary antioxidant is a phosphite.

4. The modified polyethylene double-wall corrugated pipe material according to claim 1, characterized in that: It also includes 0.2-0.5 parts of hindered amine light stabilizer.

5. The modified polyethylene double-wall corrugated pipe material according to claim 1, characterized in that: It also includes 5-10 parts of light calcium carbonate with a particle size of 1-5 μm and 1-2 parts of a titanate coupling agent.

6. The modified polyethylene double-wall corrugated pipe material according to claim 1, characterized in that: The toughening agent is ethylene-vinyl acetate copolymer.

7. The modified polyethylene double-wall corrugated pipe material according to claim 1, characterized in that: The invention also comprises a lubricant, which is calcium stearate, and the added amount thereof is 0.5-1.5 parts.

8. A method for preparing the modified polyethylene double-wall corrugated pipe material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Weigh the raw materials of each component according to the amount; (2) placing high-density polyethylene particles and linear low-density polyethylene particles in a freeze dryer and cooling them to below -50°C; (3) The polyethylene particles become brittle and hard after cooling, and are taken out and put into a ball mill for crushing. The crushed polyethylene powder is taken out from the equipment and passed through a 200-mesh sieve to obtain polyethylene powder of the desired particle size range; (4) The polyethylene powder obtained in step 3 is mixed with a cross-linking modifier, a primary antioxidant, an auxiliary antioxidant, and dicumyl peroxide in proportion, and then a grafting reaction is carried out in a reactor to obtain a grafted polyethylene powder. The reaction temperature is 150-200° C. and the reaction time is 10-20 min. During the reaction, continuous stirring is required to ensure that the materials are evenly mixed; (5) adding the remaining raw materials in sequence, and then continuing to stir and mix, and maintaining the temperature at 150-200° C., so that the remaining components are evenly coated on the periphery of the grafted polyethylene powder; (6) extruding the grafted polyethylene powder through an extruder; (7) The extruded product is immersed in warm water at 70-90°C to carry out a hydrolysis and cross-linking reaction.

Citation Information

Patent Citations

  • Room-temperature silane-crosslinked low-smoke halogen-free flame-retardant polyolefin composite and preparation method thereof

    CN107033432A

  • Low-smoke halogen-free cable material containing rare earth synergistic flame retardant and preparation of low-smoke halogen-free cable material

    CN112795077A

  • Basic magnesium sulfate whisker modified polyethylene material and preparation method thereof

    CN113234276A

  • Multifunctional polyurea coating for power battery tray as well as preparation method and application thereof

    CN113583553A

  • Silane crosslinked polyethylene resin composition for pipes and method for preparing pipes

    CN113956400A